2018
DOI: 10.1108/maj-08-2017-1634
|View full text |Cite
|
Sign up to set email alerts
|

Does external auditing combat corruption? Evidence from private firms

Abstract: Purpose This paper aims to document whether firms with audited financial statements pay lower bribes to get contracts than firms without audited financial statements. In other words, this study assesses whether external auditing helps combat corruption. Design/methodology/approach The World Bank Enterprise Survey data covering the period between 2006 and 2014 is used. The total sample comprised more than 50,000 firms in 126 countries. Findings This paper finds that firms with audited financial statements p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 34 publications
2
23
1
3
Order By: Relevance
“…The empirical evidence of the linkages between auditing and corruption are presented by several studies. Farooq and Shehata (2018) studied the ability of external auditing to combat corruption, their study of private firms found that the firms with audited financial statements paid significantly lower bribes compared to firms without an audit. Neu, Everett and Rahaman (2011) investigated auditing's role on corruption in the public sector for the case of the Canadian Sponsorship Program, and found that fraud and corruption could occur within the public sector, even in the presence of seemingly robust controls.…”
Section: Empirical Evidencementioning
confidence: 99%
“…The empirical evidence of the linkages between auditing and corruption are presented by several studies. Farooq and Shehata (2018) studied the ability of external auditing to combat corruption, their study of private firms found that the firms with audited financial statements paid significantly lower bribes compared to firms without an audit. Neu, Everett and Rahaman (2011) investigated auditing's role on corruption in the public sector for the case of the Canadian Sponsorship Program, and found that fraud and corruption could occur within the public sector, even in the presence of seemingly robust controls.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Some study showed that firms with audited financial statement pay significantly lower amounts in bribes than non-audited firms (Farooq and Shehata, 2018). In public sector, it found that audit independence and audit professionalism reduce the level of country's corruption (Gustavson and Sundstrom, 2016).…”
Section: Why Do Accounting Educators Have a Responsibility About Corrmentioning
confidence: 99%
“…Ada banyak faktor yang mempengaruhi perusahaan untuk melakukan suap salah satunya karena kurangnya perhatiaan perusahaan terhadap laporan keuangan. Farooq & Shehata (2018) menyatakan bahwa suap lebih nyata dapat terjadi di lingkungan perusahaan yang tekanannya lebih tinggi untuk terlibat dalam praktik suap.…”
Section: Pendahuluanunclassified
“…Kualitas informasi dalam laporan keuangan dapat dinilai melalui kegiatan verifikasi laporan keuangan. Farooq & Shehata (2018) menyatakan bahwa kegiatan verifikasi merupakan proses konfirmasi yang meyakinkan keberadaan aset dan liabilitas yang tertera di laporan keuangan. Kegiatan verifikasi laporan keuangan dilakukan untuk memastikan bahwa laporan keuangan perusahaan telah memenuhi karakteristik laporan keuangan yang meliputi handal, relevan, dapat dipahami dan dapat dibandingkan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation